1987
DOI: 10.1557/proc-113-107
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Fluctuations in the Physical and Chemical Properties of a High-Calcium Fly Ash

Abstract: The physical and chemical properties of fly ash produced at Ottumwa Generating Station have been monitored since April, 1985. The fly ash is produced from burning a low sulfur, sub-bituminous coal obtained from the Powder River Basin near Gillette, Wyoming. One-hundred and sixty samples of fly ash were obtained during the two year period. All of the samples were subjected to physical testing as specified by ASTM C 311. About one-hundred of the samples were also subjected to a series of tests designed to monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Several excellent reviews of fly ash chemical and mineralogical compositions and properties are given in Helmuth (1987, McCarthy (1988), Hemmings and Berry (1988), , Dudas and Warren (1988), Stevenson, et al (1988), Berry, et al (1988), Bellotto, et al (1990, Schlorholtz, et al (1988), and Kilgour and Diamond (1988), to which the reader is referred for detailed discussions of formation processes and resulting elemental and compound partitioning in fly ashes. A brief overview is given in the following discussions.…”
Section: Fly Ashesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several excellent reviews of fly ash chemical and mineralogical compositions and properties are given in Helmuth (1987, McCarthy (1988), Hemmings and Berry (1988), , Dudas and Warren (1988), Stevenson, et al (1988), Berry, et al (1988), Bellotto, et al (1990, Schlorholtz, et al (1988), and Kilgour and Diamond (1988), to which the reader is referred for detailed discussions of formation processes and resulting elemental and compound partitioning in fly ashes. A brief overview is given in the following discussions.…”
Section: Fly Ashesmentioning
confidence: 99%
“…In addition to the pozzolanic glass hydration mentioned for (Poellmann, 1990, Poellmann, et al, 1989. Strätlingite has been suggested to contribute to strength development in self-hardening high calcium fly ashes (Schlorholtz, et al, 1988), and forms from hydration of calcium aluminosilicate glasses.…”
Section: Hydration Of Intermediate and High Calcium Fly Ashesmentioning
confidence: 99%
“…However, the activity of fly ash cannot be estimated only based on the chemical composition from XRF analysis. Prior art demonstrated that fly ash had considerably different performance in concrete even though containing similar bulk chemical composition [10][11][12][13]. With EDS, according to the content of Al, Si and Ca, fly ash can be divided into several groups, possessing certain hydraulic activity [12,[14][15].…”
Section: Introductionmentioning
confidence: 99%
“…P. Chindaprasert et al[93,94] reported that the incorporation of FA and its fineness significantly affected on the total porosity and pore size of blended cement systems having FA.However, the civil engineering applications of blended FA-cementing materials continue having a practical challenge due to a wide variability and heterogeneity of FA. When many researchers[44,95] studied the wide variation of FA, their results showed that the when mixing cement with FA having different chemical compositions led to changes in compressive strengths, pore-size distribution, and its ability to resist chloride concentration even though such FA came from the same power plant. This is due to the combustion condition, surrounding environmental conduction during firing, and composition of the raw feed[96,97] Wang et al (2019…”
mentioning
confidence: 99%
“…Therefore, both have similar compressive strengths at 90 days. According to Schlorholtz et al[95], although fly ash for different batches were obtained from the same power plant, the performance of final product of fly ash-cement composite can be remarkably different.Because fly ash is a pozzolan, its reaction to cement delivers enhanced concrete quality through the pozzolanic reactions. Pozzolanic materials react with Ca(OH)2 phase and H2O to form compounds with cementitious properties.…”
mentioning
confidence: 99%